An Analysis of the Instructors’ Techniques in Teaching English Vocabulary at MY LIBERTY International English School - Gani, Rifkah; Napu, Novriyanto; Umar, Irmawaty (Transbahasa, 2024)
This study discusses the techniques used in teaching English vocabulary to young learners at MY LIBERTY International English School. The theoretical significance of the research lies in its potential to enhance readers' knowledge about effective teaching techniques for young learners. Additionally, this research can be a reference for future researchers exploring similar topics. The study aims to analyze the techniques employed by instructors in teaching English vocabulary to young learners and to evaluate students' responses to these techniques. A qualitative descriptive methodology was used, with observation sheets and interviews serving as the primary data collection methods. The researcher conducted interviews with three instructors and nine students to supplement the observational data. The results of the study indicate that out of nine identified techniques, eight were actively used by the instructors. These techniques include repetition, the use of pictures, pronunciation drills, modeling/demonstration, providing clues, games, question and answer sessions, and reading aloud. One technique was not observed in the teaching process. Understanding students' responses to these teaching techniques is crucial for instructors as it provides valuable feedback for improving their teaching strategies. The analysis of student responses revealed that out of the nine respondents, seven students had positive reactions, while two students had negative responses.